2020
DOI: 10.1136/ijgc-2020-001973
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus clinical staging prior to primary chemoradiation in patients with cervical cancer FIGO stages IIB–IVA: oncologic results of a prospective randomized international multicenter (Uterus-11) intergroup study

Abstract: ObjectiveRevised staging of patients with locally advanced cervical cancer is based on clinical examination, imaging, and potential surgical findings. A known limitation of imaging techniques is an appreciable rate of understaging. In contrast, surgical staging may provide more accurate information on lymph node involvement. The aim of this prospective study was to evaluate the impact of pre-treatment surgical staging, including removal of bulky lymph nodes, on disease-free survival in patients with locally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 33 publications
2
56
1
3
Order By: Relevance
“…Thus, laparoscopic staging is widely applied leading to upstaging in > 30% of locally advanced cervical cancer patients and allowing for treatment triage (radical hysterectomy versus definitive RCHT). Recently, the randomized trial Uterus-11 has shown that laparoscopic staging did not only avoid under-or overtreatment, but had an impact on disease-free survival and cancer-specific survival, respectively, without increased toxicity rates [137].…”
Section: Cervical Cancermentioning
confidence: 99%
“…Thus, laparoscopic staging is widely applied leading to upstaging in > 30% of locally advanced cervical cancer patients and allowing for treatment triage (radical hysterectomy versus definitive RCHT). Recently, the randomized trial Uterus-11 has shown that laparoscopic staging did not only avoid under-or overtreatment, but had an impact on disease-free survival and cancer-specific survival, respectively, without increased toxicity rates [137].…”
Section: Cervical Cancermentioning
confidence: 99%
“…The recent results of the prospective trial Uterus-11 showed no differences in OS and PFS globally, although a significant benefit in DFS was found for patients with FIGO stage IIB and, in a post-hoc analysis, a cancer-specific survival benefit in favor of laparoscopic staging (27). However, in this study aortic lymphadenectomy was performed at the same time as pelvic lymphadenectomy, even in those cases that presented bulky pelvic nodes, and therefore the effects only at the pelvic level were not evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…A prospective trial evaluated the use of laparoscopic staging after (false) negative FDG-PET/CT and showed significantly superior oncological outcomes for patients with lymph node metastases < 5 mm vs. > 5 mm after surgical staging and RCHT [141]. The shortcoming of the above mentioned Uterus-11 trial [137] is that FDG-PET/CT was not used in that study. The idea of combining the validation of FDG-PET/CT and laparoscopic staging has been discussed by the LilACS study group.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Thus, laparoscopic staging is widely applied leading to upstaging in > 30 % of locally advanced cervical cancer patients and allowing for treatment triage (radical hysterectomy versus definitive RCHT). Recently, the randomized trial Uterus-11 has shown that laparoscopic staging did not only avoid under-or overtreatment, but had an impact on disease-free survival and cancer-specific survival, respectively, without increased toxicity rates [137]. Laparoscopic staging therefore remains the gold standard for FIGO stage IIB and >IIB patients [137][138][139].…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation